Multiband UWB Trapezoidal Antenna Using U and Pi-Shaped Slots - Noor Zirwatul Ainee, Naharuddin; Nurul Hazlina, Noordin (IEEE, 2015)
This paper presents the analysis of CPW-fed trapezoidal monopole antenna added with parasitic elements and slots. From previous work, the proposed antenna altered by adding parasitic elements to enhance the operation bandwidth and achieved frequencies from 3.2GHz to 11.5GHz which covered Ultra Wide Bandwidth. This antenna is fabricated on FR4 for real measurement. Next experiment continues with slots insertion to generate notch and reconfigure frequency. U and slots applied on trapezoidal patch. The antenna’s performance observes through adjustment of slot’s dimension.